THE ASSOCIATIVISM AS A STRATEGY TO FACE UP A COMPETITIVE MARKET: A CASE STUDY OF SMALL PHARMACEUTICAL COMPANIES - Saavedra García, María Luisa (2012)
The objective of this research is to demonstrate the existence of a real need on the part of pharmaceutical companies to partner with in order to obtain trade and financial advantages resulting from joint purchasing and coordination of marketing activities. The methodology used was the analysis of a case, taking as unit of analysis a “Pharmacy Association” of Argentina. The main findings of this research show that it is possible to apply the associativism to this type of organizations and it is possible to achieve a coordinated merchandise action and applying marketing strategies. There are more advantages than disadvantages of applying this tool.